(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The expansion of city is the reason for conversion of agricultural land into non-agriculturalland. Therefore, the assessment of occupation structure before expansion and after expansion onexpanded area is necessary. In the year 2001 in expansion of Pune city about 23 villages are mergedin Pune city. Therefore, to assess change in occupation structure of these villages here attempt hasbeenmadetoassesstheoccupationofthese23villagesfrom1981to2011.Toassessthisoccupation structure the nine industrial categories of workers are considered. The study showschange in socio economical condition of these 23 villages after insertion in city. It shows that due tomerge in the Pune city the population engaged in primary activities is decreased from decades todecade but population in tertiary and secondary activity has been increased.In tertiary activitiestheyaremajorityengagedin constructionand transportationbusiness andthen inservicesector.